Metal-organic framework-derived hierarchical porous carbon fiber bundles/Y2Co8Fe9 composite as a thin and broadband electromagnetic wave absorber. (August 2022) - Lou, Yaxin; Zhang, Zhihua; Tan, Guoguo; Man, Qikui; Chen, Shuwen; Kang, Yiyu; Zhong, Jinpeng; Lei, Zhenkuang
Highlights: MOF-derived porous carbon fiber bundles/Y2 Co8 Fe9 composites were prepared. Good impedance and attenuation were obtained due to the synergetic effect. The maximum RL of -64.79 dB and bandwidth of 5.02 GHz were obtained at 1.44mm. A broad bandwidth of 6.52 GHz was acquired at 1.6 mm. Absorption mechanisms were discussed. Abstract: The development of broadband and thin electromagnetic wave absorbing materials is urgently required for use in practical applications. In this study, microwave absorption composites comprising Y2 Co8 Fe9 and various weight ratios of metal-organic framework (MOF)-derived carbon fiber bundles (0%, 0.1%, 0.3%, 0.5%) were prepared. The composite filled with 0.1 wt% MOF-derived carbon fiber bundles had a minimum reflection loss (RL) of -64.79 dB at a thickness of 1.44 mm and an effective absorption bandwidth (with an RL of less than -10 dB) of 5.02 GHz. Furthermore, a wide effective absorption bandwidth of 6.52 GHz was also acquired at 1.6 mm. The microwave absorption performance was significantly enhanced owing to the improved impedance matching, as well as the synergetic effect between the dielectric loss and magnetic loss. This study provides a new paradigm for fabricating composites consisting of MOF-derived materials and rare-earth materials for thin and broadband microwave absorption performance. Graphical Abstract: Image, graphical abstract